Anaphylaxis in pregnancy in the USA: Risk factors and temporal trends using national routinely collected data - McCall, S; Kurinczuk, J; Knight, M (Elsevier, 2019)
Background: Anaphylaxis in pregnancy is an understudied, rare, and severe complication of pregnancy.